Bridging the gap: communities, forests and international networks - Colchester, M. (2003)
Community forestry has transformed over the past 25 years from being an experimental means of providing wood-fuel for the rural poor to a community-led movement demanding reform of the forestry sector. International networks to promote community forestry, which emerged at very different moments in this history with different visions, goals, targets and participants, have played a key role in this transformation. Based on a review of seven countries and ten networks, the study compiles the main lessons learned from this experience in term of effectiveness, communications techniques, network governance, relations with donors and linkage to social movements. The increasing mobilisation of community-based organisations means that supportive NGOs and government agencies now need to play a different role to the one they gave themselves 25 years ago.